Analysis Of Service Quality On Satisfaction Customers On Telkomsel Cards With Confirmatory Factor Analysis Method - Rahmi, Ruslina (Jurnal Info Sains : Informatika dan Sains, 2024)
PT.  Cellular  Telecommunications  or  in  short  Telkomsel  is  a  subsidiary  of  Telkom  Indonesia  which  operates  in  the  telecommunications  sector  for  individual  consumers  (until  2023  it  only  deals  in  cellular  telecommunications). The  more  mobile  companies  develop,  the  tighter  the  competition  between  companies  becomes,  so  there  is  a  need  for  an  analysis  that  discusses  the factors  that  have  the  most  influence  on  the  company's  development,  one  of  which  is  by  looking  at  customer  satisfaction  factors.  The  progress  of  a  company  is  influenced  by  the  company's  ability  to  serve  its  customers. In  terms  of  services  offered  by  the  company,  it  is  necessary  to  pay  attention  that  the  quality  standards  offered  to  customers  must  exceed  customer  expectations, so  that  customer  satisfaction  can  be  easily  achieved  by  the  Company.  In  statistics,  there  are  several  factor  analysis  methods,  including  Exploratory  Factor Analysis  (EFA)  and  Confirmatory  Factor  Analysis  (CFA) .  The  confirmatory method  is  a  multifarious  method  that  can  be  used  to  test  or  confirm  a hypothesized  model. This  method  is  a  measurement  method  in  multivariate  equation  modeling.  This  model  is  more  flexible  compared  to  the  general  classical  approach.  From  the results  of  research  conducted  using  two-stage  confirmatory  factor  analysis, several  conclusions  can  be  put  forward  that  the  indicators  that  influence  service quality  on  customer  satisfaction  on  Telkomsel  cards  using  the  Confirmatory Factor  Analysis  (CFA)  method  are  the  total  contribution  made  by  service  quality to  customer  satisfaction  at  PT  Telkomsel  is  equal  to 0.824.  This  shows  that  the  service  quality  dimension  which  measures  the  customer  satisfaction  variable  can  explain  this  influence  by  82.4%.